2021
DOI: 10.1016/j.optom.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of optometrist practice type on NHS funded sight test outcome

Abstract: Purpose The United Kingdom (UK) National Health Service (NHS) currently provides sight tests at no cost to patients for all those aged <16 or ≥60. Some ‘at-risk’ patients and those in receipt of means-tested benefits are eligible for a NHS sight test between the ages of 16 and 60. In the UK, community optometrists typically either work in independent or national chain practices (multiples). The present study aims to explore whether practice type has any association with sight test outcome. As sigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…It is reassuring that 99.3% (397/400) of optometric practices in this sample were willing to examine children's eyes, although 85% would not examine children below a certain age (median 4 years). Our findings are in line with earlier studies, which reported that some optometrists are reluctant to examine very young children 23,25 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is reassuring that 99.3% (397/400) of optometric practices in this sample were willing to examine children's eyes, although 85% would not examine children below a certain age (median 4 years). Our findings are in line with earlier studies, which reported that some optometrists are reluctant to examine very young children 23,25 …”
Section: Discussionsupporting
confidence: 93%
“…Despite the fact that community optometrists are well placed to play an important part in children's eye care, a telephone survey conducted in 2007 reported that 2% of practices would not carry out an eye examination on a child until the age of 7 years and that 54% of practices would exclude young children (aged 1 year) from a General Ophthalmic Services (GOS) eye examination 23 24 and the median age at which a child's first sight test is conducted in one region of England is 6 years 25 . One study exploring the effect of optometrist practice type on children's first NHS sight test 25 reported that children under the age of 16 attending a multiple practice were more likely to receive a new or changed prescription than those attending an independent practice.…”
Section: Introductionmentioning
confidence: 99%
“…An often cited source dates back to 2015 1 . Recently, an analysis by Swystun and Davey of over 650 000 GOS‐ST forms revealed an overall RR of 5.1% 14 . A limitation of this approach is that COs may forget to tick the GOS‐ST box indicating referral since the form is not part of their clinical records and this information from the GOS‐ST is not regularly audited.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of optometric referrals have typically studied those patients that reach the HES, 6–13 and provide no data on what proportion of optometric referrals are seen in the HES. A recent analysis of 664 480 GOS‐ST forms reveals an overall referral rate of 5.1%, with patients aged 60 years and above being four times more likely to be referred than children 14 . This research concentrated on the initiation of referrals, and there is a dearth of studies that investigate optometric referrals from their initiation through to the HES appointment and any consequent correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…Also previous research from the UK has indicated that there are differences in the outcomes from eye examinations conducted in independent and corporate practises. 33 34 However, a recent questionnaire study in Northern Europe (Denmark, Sweden, Norway, Finland and the Netherlands), concludes that there is a similar level of optometry competency across the countries and further there is only a minor difference between new and experienced optometrists with more than 5 years of practising. 35 Supported by these factors, the authors suggest that this study is highly relevant for any optometry retail company in the region.…”
Section: Discussionmentioning
confidence: 99%